Notes on some bryophilous Pezizales (Fungi) in the Mediterranean part of Bosnia and Herzegovina - Nedim Jukić; Smiljan Tomić; Marko Sabovljević; Nihad Omerović (Glasnik Šumarskog Fakulteta Univerziteta u Banjoj Luci, 2018)
Results from bryomycological field studies in the Mediterranean part of Bosnia and Herzegovina are reported in the paper. Five bryophilous taxa of ascomycetes have been recorded on few locations around the city of Neum and on the Klek peninsula. Three of them are new for the mycobiota of Bosnia and Herzegovina – Octospora gemmicola, Lamprospora miniata var. parvispora and Lamprospora miniata var. ratisbonensis.